Measuring Job Satisfaction Among Primary School Managers - Taha, Nashwan Khalaf; Jassim, Khaled Ahmed (Journal of Tikrit University for Humanities, 2023)
The current research aims to identify the level of organizational excellence among primary school Managers and to know the statistically significant differences in the occupational satisfaction of the variables of sex (male-female) and the number of years of service (less than 1-5 years) (6 and above). The current research community consisted of principals of primary schools in Salah al-Din Governorate, districts (Tikrit-Baiji-Sharqat) for the academic year (2021-2022), and their number was (429) principals, while the total research sample amounted to (350) principals, and the validity of the study was verified. The two scales were adopted by adopting (apparent validity and construct validity) and the discriminatory power of the items of the two scales was calculated As for the stability, it was calculated using the retest method, and Cronbach’s alpha for both scales, and the data were statistically treated using the statistical package (SPSS). Females, as for the variable years of service, the results showed that the managers of the research sample who have service less than (5) years have a higher degree of professional satisfaction than managers with service more than (6) years.